On Teaching: “Making Globalization Ordinary: Using the Web to Teach Globalizatio - Tackacs, Stacy (American Studies, 2010)
“Making Globalization Ordinary” examines the challenge posed by globalization to traditional conceptions of the nation-state and offers a case study for how to address these transformations in the introductory American Studies class context. It is particularly geared toward colleges and universities in the Mid-American region where circumstances encourage students to think of globalization as a distant and relatively unimportant problem. It seeks to provide answers to the following questions: How do you teach about globalization in areas where the most destabilizing effects of capitalist transformation seem unrelated to daily life? Where global migrations increasingly affect local conditions, but in ways that are obscured by persistent patterns of ethnic, racial, and class privilege? Where politicians, economic leaders, and heritage industries all tout the timelessness of “local values” and encourage a willful blindness to the global penetration and reconfiguration of the local?